Charlotte Brontë's Jane Eyre (Chelsea House Publ., 1987)
A selection of seven critical essays on Charlotte Bronte's greatest novel, arranged in chronological order of publication.
Keywords: Aufsatzsammlung; Brontë; Charlotte <1816-1855>; Brontë; Charlotte; Jane Eyre; Governesses in literature